APLIKASI SISTEM PENDETEKSI KADAR GAS BUANG KENDARAAN BERMOTOR - Bayu Nugroho (Jurnal Informatika, 2011)
Sources of air pollution one of them is motor vehicle exhaust gas, the gas produced from the combustion of fuel occurs at vehicle engine. Application detection level of the exhaust system of motor vehicles that are made used to detect the amount of gas levels of NO and CO gases using the sensor TGS2201. Data from sensors is processed by the microcontroller and the results are displayed on the PC through serial port, the design of an application program using the Delphi programming language. Keywords: gas, microcontroller, sensors, and TGS2201